Perancangan Sistem Otomatisasi Pengomposan Pupuk Organik Cair dengan Sensor Suhu Berbasis Internet of Things - Widya Rohmatusfaida (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Organic waste management is a significant environmental challenge, yet it has the potential to produce valuable products such as liquid organic fertilizer. Conventional composting processes tend to be inefficient and require manual intervention. This study aims to design and implement an automated composting system for liquid organic fertilizer based on the Internet of Things (IoT) using the ESP32 microcontroller, DS18B20 temperature sensor, and actuators including a pump, exhaust fan, and stirring motor. The system is designed with temperature set-point-based control logic, where actuators are automatically activated when the temperature falls below 25 °C or rises above 50 °C. Testing was conducted in two stages: without load and with organic material load. Temperature sensor calibration results showed high accuracy with an average error of 0.08 °C and precision with a standard deviation of 0.2 °C. The system proved capable of operating independently, responding quickly to temperature changes, and integrating with the Ubidots and Telegram platforms for real-time monitoring and notifications. The main contribution of this research is the implementation of a temperature-based automatic control system integrated with IoT, which differs from previous studies that mostly focused only on monitoring functions.